Using social media to explore the linguistic features in female adults with childhood sexual abuse by Linguistic Inquiry and Word Count. Issue 3 (26th July 2019) - Wan, Wenyu; Sun, Jiumo; Liu, Jiehan; Yang, Shu‐Wen; Liu, Mingming; Xue, Jia; Jiao, Dongdong; Liu, Xiaoqian
Abstract: The adverse impact of childhood sexual abuse experience on a person's physical and mental health is long‐lasting. The disadvantageous influence can be reflected in the language expression even if they grow up, especially when the language is not monitored intentionally by the speaker. However, few researchers have focused on the language expression characteristics of this group. This study aims to analyze the message of social media to explore the difference of language expression between adult females with childhood sexual abuse experience (CSA group) and adult women without such experience (control group) by Linguistic Inquiry and Word Count (LIWC). We collected 46 victims (all females) and 46 nonvictims (gender‐matched with CSA group) on Sina Weibo, and we applied LIWC to encode and count all the text messages posted on the social platforms. The results of this research suggested that the CSA group differed from the control group in multiple indicators, especially in psychological process words. The victims were less likely to refer to psychological process words, such as body words, sex words, etc. than the nonvictims, however, they preferred to mention human words. Moreover, compared to the control group, the CSA group had published fewer contents and used fewer words that represent the present tense in the social media platforms. The present study provides the research basis for identifying the CSA group in social media platforms in the future.